Suggestions for resin research under the COST Action EU-PoTaRCh [version 2; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Jakub Brózdowski; Vítor João Pereira Domingues Martinho (Open Research Europe)
Forest management and planning are often challenging, specifically because of the irregular income flow available to landowners. In timber production, for example, producers must wait several years before receiving returns on their investments in forested land. As a result, such economic uncertainty can make forest activities less attractive to investors and discourage effective management strategies. The forest by-products appear as an opportunity to increase the profitability of the forest lands and motivate the landowners for more effective planning. This is crucial, namely in countries where, for example, forest fires are real problems for economic activity, populations and the environment. In this context, this study, developed within the scope of the COST Action EU-PoTaRCh, intends to bring more insights and suggestions for the scientific research about resin. To give suggestions, a search was performed in the Scopus database (article title, abstracts and keywords), on 02 November 2024, for the following topics: “natural resin” or “plant resin”. In the search, 4127 documents were obtained and assessed through bibliometric analysis. The results obtained show that scientific research has focused mainly on biological and chemical aspects, while social, economic, cultural, and policy dimensions remain unexplored. The study suggests promoting transdisciplinary and international collaboration, principally in countries with limited research on resin, to support more comprehensive and inclusive policies and strategies on forest by-product.